Sonja Sekula & Friends - Fetzer, Fanni; Kunstmuseum Luzern, Luzern; Pollock, Griselda; Müller, Dominik (Zürich : Verlag Scheidegger & Spiess AG, 2016)
Barrell, Robert ; Bourgeois, Louise ; Busa, Peter ; Cornell, Joseph ; Duchamp, Marcel ; Ernst, Max ; Greene, Balcomb ; Gorky, Arshile ; Hélion, Jean ; Lam, Wifredo ; Matta, Roberto ; Motherwell, Robert ; Nevelson, Louise ; Newman, Barnett ; Pollock, Jackson ; Rahon Paalen, Alice ; Rothko, Mark ; Seligmann, Kurt ; Vieira da Silva, Maria Helena ; Taeuber-Art, Sophie ; Tobey, Mark ; Walker, Bradley ; Wheeler, Steve
This book is published on the occasion of the exhibition Sonja Sekula, Max Ernst, Jackson Pollock & Friends. Kunstmuseum Luzern. June 11 - September 25, 2016
boek
Keywords: Sekula, Sonja